Heartwater and the economics of livestock production on large scale commercial and smallholder farms in Zimbabwe - Chamboko, Tafireyi; Mukhebi, A.W.; O'Callaghan, C.J.; Peter, T.F.; Kruska, Russell L.; Medley, G.F.; Mahan, S.M.; Perry, Brian D. (1999)
In order to assess the economic impact of heartwater (Cowdria ruminantium infection) and model the impact of improved vaccines against the disease, a field study was conducted to provide data on livestock productivity indicators in Zimbabwe. Cross-sectional studies were performed in the two main agro-ecological regions, lowveld and highveld, where heartwater was thought to be endemically stable and epidemic, respectively. These studies were designed to provide data on livestock productivity and profitability, and other key production indicators from the smallholder (SH) and large scale commercial (LSC) production systems, and from beef, dairy, sheep and goat enterprises. The results show that the profitability of LSC beef farms, as indicated by overall positive gross margins, was similar (p>0.05) irrespective of location and whether or not heartwater cases were reported. Only LSC dairies that reported heartwater cases demonstrated a negative gross margin, though this was not significantly different from dairy farms that did not report heartwater, or from the beef farms. The highveld and lowveld SH areas, which were both assumed to be endemically stable for heartwater, displayed positive gross margins, though the margin was significantly (p<0.001) higher in the highveld than in the lowveld. This study indicates that losses associated with heartwater are minimal under endemic stability and in epidemic areas where tick control is effectively implemented. Furthermore, the profitability of livestock production, in both the LSC and SH production sectors, could be increased if more cost effective methods of tick and tick-borne disease control (which is one of the major costs of production) are made available.